Desecration of Corpses in Relation to 8(1) no. 9 German Code of Crimes against International Law (VStGB): The Judgment of the German Federal Court of Justice (Bundesgerichtshof) of July 27, 2017-3 StR 57/17 - Bergmann, Vanessa; Blenk, Franziska; Cojger, Nathalie (German Law Journal, 2021)
As a reaction to the killing and beheading of two soldiers in the Syrian Civil War, the German Federal Court of Justice (BGH) set a milestone in the interpretation of 8(1) no. 9 of the German Code of Crimes against International Law (VStGB). The judges confirmed the conviction of a young German citizen with Syrian roots, Aria L., who had been tried and convicted before the Higher Regional Court of Frankfurt am Main (Oberlandesgericht (OLG) Frankfurt am Main). Within the certiorari, the BGH reviewed whether the statute conformed with the principle of legality found within the Grundgesetz (GG), Germany's constitution. The Court held that the corpse of a person killed is protected from desecration under humanitarian law pursuant to 8(1) no. 9 VStGB, the equivalent to ArticleÂ 8(2)(b)(xxi) and (3)(ii) of the Rome Statute for the International Criminal Court (ICC). Reviewing this particular decision, it was determined that under the circumstances of a non-international armed conflict, beheading someone, placing the head on a metal rod, and taking pictures afterward in order to upload them onto social media is gravely humiliating and degrading. The head is incomparably the part of the body that identifies a person. Furthermore, it is irrelevant whether the perpetrator had any physical influence over the person. In addition, war crimes can be committed in a non-international conflict, which should, however, be treated equally as an international conflict. This outcome triggered diverse reactions amongst legal scholars, especially due to the extension of the understanding of a person who is to be protected under humanitarian law.
CRIS-Team Scopus Importer:2021-11-19
Keywords: desecration of corpses; German criminal law; humanitarian law; International criminal law; person to be protected under international humanitarian law; Syrian Civil War; war crimes